Arctic politics, the law of the sea and Russian identity - Geir Hannoland (Palgrave pivot, 2014)
This book analyses the Russian opposition to the 2010 Barents Sea delimitation agreement in light of both the Law of the Sea and Russian identity, arguing that the agreement's critics and proponents inscribe themselves into different Russian narratives about Russia's rightful place in the world.